Artist to artist 23 major illustrators talk to children about their art. - Carle, Eric.; Philomel Books; Eric Carle Museum of Picture Book Art. (New York Philomel Books, 2007)
Twenty-three illustrators of children's literature discuss their lives, inspirations, and creative backgrounds and present photographs of themselves and their work spaces along with examples of their illustrations.
A note from Eric Carle -- Mitsumasa Anno -- Quentin Blake -- Ashley Bryan -- Nancy Ekholm Burkert -- Eric Carle -- Tomie dePaola -- Jane Dyer -- Mordicai Gerstein -- Robert Ingpen -- Steven Kellogg -- Leo Lionni -- Petra Mathers -- Wendell Minor -- Barry Moser -- Jerry Pinkney -- Alice Provensen -- Maurice Sendak -- Gennady Spirin -- Chris Van Allsburg -- Rosemary Wells -- Paul O. Zelinsky -- Robert Sabuda & Matthew Reinhart -- A note from Nick Clark, museum director -- Biographies of the artists.
Unique anthology of twenty three artists have shared the story of their work, their art and their lives as creative people and were among the first to exhibit their work at the Eric Carle Museum of Picture Book Art.
Keywords: Eric Carle Museum of Picture Book Art; Illustrators; Children's literature -- Illustrations; Illustration of books; Illustrators -- Biography; Picture books for children; Illustration of books